A Review of Neurological Symptoms in Long COVID and Clinical Management - Navis, Allison (Seminars in Neurology, 2023)
Long COVID is a clinical diagnosis generally referring to the persistence or development of new symptoms, affecting multiple organ systems after SARS-CoV-2 COVID-19 infection. Long COVID is thought to affect ∼20% of people after infection, including all age ranges and severity of infection. Fatigue, postexertional malaise, and respiratory and cardiac symptoms are commonly described. Neurological symptoms such as cognitive changes, sensory disturbances, headaches, and dysautonomia are common as well. The underlying pathophysiology remains unclear but immune dysregulation, autoimmunity, persistent viral reservoirs, and microvascular dysfunction have been implicated. As there are no tests at this time to diagnose long COVID, work-up should be focused on assessing reversible or treatable causes of symptoms. Furthermore, no treatments for long COVID currently exist, and management remains focused on a multimodal approach and symptom management, with many people showing improvement in symptoms over time.
Keywords: fatigue; brain fog; dysautonomia; headache; neuropathy